2019
DOI: 10.1108/imds-02-2018-0088
|View full text |Cite
|
Sign up to set email alerts
|

The impact of lean practices on the operational performance of SMEs in India

Abstract: Purpose: Although lean thinking is deemed to be a gold standard of modern production management, a lot of scepticism still remains regarding its applicability in small and medium-sized enterprises (SMEs). This paper aims to understand the perception of lean in SMEs and establish the relationship between lean adoption and operational performance.Design/Methodology/Approach: With the help of a survey, data was collected from 425 SMEs in India and analyzed using structural equation modelling (SEM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 42 publications
6
64
0
1
Order By: Relevance
“…Vanichchinchai (2014) reported that the level of lean system and partnership management in large companies in the Thai automotive supply chain was higher than those in small and medium companies. More recently, Yadav et al (2019) explored the effect of LM on operational performance of small and medium sized enterprises in India. They found that small and medium sized enterprises adopt a limited number of LM practices.…”
Section: Reliability and Validitymentioning
confidence: 99%
“…Vanichchinchai (2014) reported that the level of lean system and partnership management in large companies in the Thai automotive supply chain was higher than those in small and medium companies. More recently, Yadav et al (2019) explored the effect of LM on operational performance of small and medium sized enterprises in India. They found that small and medium sized enterprises adopt a limited number of LM practices.…”
Section: Reliability and Validitymentioning
confidence: 99%
“…We compared these findings with empirical studies that reported statistically significant relationships between EME and lean practices, and we observed differences in the sample context. For example, studies that investigated SME process industries (Marin-Garcia and Bonavia, 2015), SME manufacturing firms (Godinho Filho et al , 2016), SME manufacturing firms (Knol et al , 2018) and SMEs (Yadav et al , 2019a) reported statistically significant results for the employee-related social practices. The differences in the sample context as an explanation of the apparent inconsistencies on the relationship between EME and lean practices indicate boundary conditions for lean relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review conducted in Section 2 identified ORA, ITP, EME, SUP and CUS as the five theoretical constructs representing the social and technical aspects of lean implementations. The existing survey instruments on lean implementations such as Shah and Ward (2007) and Yadav et al (2019a) have mainly focussed on the technical practices, supplier- and customer-related lean practices. Malmbrandt and Åhlström (2013) included the social practices in their proposed instrument, but no scale for measuring the ORA for lean implementation exists.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has largely been found to improve operational performance in areas of operational flexibility, dependability, speed while minimising inventoryrelated costs [65,67,68,69]. Other studies similarly found JIT to positively influence operational performance in terms of timely deliveries, waste elimination, increased productivity while improving demand management [70,71,72]. The study hypothesised that; H5: Just In Time significantly improves operational performance of manufacturing firms.…”
Section: Just In Time and Operational Performancementioning
confidence: 91%